Model Application of Entomopathogenic Fungi as Alternatives to Chemical Pesticides: Prospects, Challenges, and Insights for Next-Generation Sustainable Agriculture - Bamisile, Bamisope Steve; Akutse, Komivi Senyo; Siddiqui, Junaid Ali; Xu, Yijuan (Frontiers in Plant Science, 2021)
In the past few decades, the control of pests and diseases of cultivated plants using natural and biological measures has drawn increasing attention in the quest to reduce the level of dependence on chemical products for agricultural production. The use of living organisms: predators, parasitoids, and microorganisms such as viruses, bacteria, and fungi, has proven to be a viable and sustainable pest management technique. Among the aforementioned, fungi, most importantly the insect pathogenic species, have been in use for more than 150 years. These include the most popular strains belonging to the genera Beauveria, Metarhizium, Isaria, Hirsutella, and Lecanicillium. Their application is usually through an inundative approach, which inherently involves exposure of the fungal spores to unfavorable humidity, temperature and solar radiation conditions. These abiotic factors reduce the persistence and efficacy of these insect pathogenic fungi. Despite these limitations, over 170 strains have been formulated as mycopesticides and are available for commercial use. In the last few decades, numerous studies have suggested that these species of entomopathogenic fungi offer far more benefits and have broader ecological functions than hitherto presumed. For instance, aside from their roles as insect killers, it has been well established that they also colonize various host plants and hence, provide other benefits including plant pathogen antagonism and plant growth promotion, and serve as sources of novel bioactive compounds and secondary metabolites, etc. In this light, the potential of entomopathogenic fungi as alternatives or perhaps as supplements to chemical pesticides in plant protection is discussed in this review. The paper highlights the numerous benefits associated with endophytic fungal entomopathogen and host plant associations, the mechanisms involved in mediating plant defense against pests and pathogens, and the general limitations to the use of entomopathogenic fungi in plant protection. A deeper understanding of these plant host-fungus-insect relationships could help unveil the hidden potentials of fungal endophytes, which would consequently increase the level of acceptance and adoption by users as an integral part of pest management programs, and as a suitable alternative to chemical inputs toward sustainable crop production.